Effects of love glove application on vital signs for COVID‐19 patients in the intensive care unit - Funda Karaman; Asli Genc; Ayse Nur Yerebakan Sen; Mahruk Rashidi; Gulay Yildirim; Gulsah Unsal Jafarov; Rabia Acar; Buse Saygin Sahin (Wiley, 2024)
Abstract Aim To evaluate the effects of love glove application on vital signs for COVID‐19 patients in the intensive care unit. Design A single‐group pretest‐posttest quasi‐experimental design was used. TREND Statement Checklist was followed during the present study. Methods The study was conducted on 30 intubated/extubated adult patients. The gloves were filled with warm water and air to prevent pressure injuries. Then they were tied together and applied to both hands of the patient for 30 min. The patient's vital signs were recorded before and after the application. A Wilcoxon signed‐rank test was performed. Results It was determined that respiratory rate, systolic blood pressure, diastolic blood pressure and oxygen saturation were significantly affected after the application of the love glove. The application of love gloves is a cheap and non‐pharmacological method with no side effects. Patient or Public Contribution Patients were involved in the design and conduct of this study.